2014
DOI: 10.1111/acel.12226
|View full text |Cite
|
Sign up to set email alerts
|

Inbred mouse strains reveal biomarkers that are pro‐longevity, antilongevity or role switching

Abstract: Traditionally, biomarkers of aging are classified as either pro-longevity or antilongevity. Using longitudinal data sets from the large-scale inbred mouse strain study at the Jackson Laboratory Nathan Shock Center, we describe a protocol to identify two kinds of biomarkers: those with prognostic implication for lifespan and those with longitudinal evidence. Our protocol also identifies biomarkers for which, at first sight, there is conflicting evidence. Conflict resolution is possible by postulating a role swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
(48 reference statements)
4
16
0
Order By: Relevance
“…This is further strengthened by the robustness of dysregulation measures to the inclusion or exclusion of individual biomarkers. Correlations of individual biomarkers with age vary substantially across populations and must be interpreted with caution (Cohen et al ., 2015b); likewise, the same biomarker can have both pro‐ and anti‐longevity associations at different points in the lifespan (Moeller et al ., 2014). These findings might arise because aging involves a mix of non‐adaptive (i.e., pathological) changes, as well as other compensations to these changes.…”
Section: Discussionmentioning
confidence: 99%
“…This is further strengthened by the robustness of dysregulation measures to the inclusion or exclusion of individual biomarkers. Correlations of individual biomarkers with age vary substantially across populations and must be interpreted with caution (Cohen et al ., 2015b); likewise, the same biomarker can have both pro‐ and anti‐longevity associations at different points in the lifespan (Moeller et al ., 2014). These findings might arise because aging involves a mix of non‐adaptive (i.e., pathological) changes, as well as other compensations to these changes.…”
Section: Discussionmentioning
confidence: 99%
“…43 Histopathology, when done by experienced personnel, has, for over 150 years, been the stand-alone standard for arriving at a diagnosis. By contrast, physiological phenotyping approaches reflect human clinical practice and, in the context of model organisms, are often applied later in hypothesis driven approaches to understanding phenotypes as confirmatory assays selected on the basis of histopathology findings.…”
Section: Discussionmentioning
confidence: 99%
“…The mtFVB strain, harboring the amino acid exchanging polymorphism, showed a more distinct but not a significantly different increase of LSK cells from young to advanced-aged animals compared to the reference mtAKR. While aging HSCs were shown to increase with time (2,25), it was indicated that elevated ROS in vivo 30: 751-760 (2016) 756 levels in C57BL/6 mice led to an attenuated HSC maintenance and repopulation capacity (13). Furthermore, a more quiescent behavior of HSCs with higher maintenance capacity and less cycling was linked to low intracellular ROS levels (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an immune shift in aged individuals has been described, leading to a higher percentage of myeloid cells with a concomitant enhanced susceptibility to infections and development of anemia (1,2). Clinically, elderly individuals are more affected by myelodysplastic syndromes (MDS) and leukemia (3).…”
Section: Encodes For the Respiratory Chain Proteins Genetic Alteratimentioning
confidence: 99%